Host range and distribution pattern of papaya mealy bug, Paracoccus marginatus Williams and Granara de Willink (Hemiptera : Pseudococcidae) on selected Euphorbiaceae hosts in Kerala - Chellappan, Mani; Lawrence, Lince; Indhu, P; Cherian, Tom; Anitha, S; maria, Jimcy (Journal of Tropical Agriculture, 2013)
Papaya mealy bug, Paracoccus marginatus Williams and Granara de Willink (Hemiptera: Pseudococcidae) has a wide host range. In Kerala, during 2010 – 12 periods, 95 host plants were recorded belonging to 39 plant families. Highest number of host plants of P. marginatus was recorded under the family Euphorbiaceae. Heavy population build up was recorded on 44 host, moderate incidence on 27 plants and on 21 hosts, the infestation severity was low. Spatial distribution studies showed that the variance to mean ratio was the highest on Manihot esculenta Crantz (>100) and lowest on Phyllanthus amarus Schumach & Thonn. (0.63). Members of the same genus had variation in different indices owing to the plant architecture.